Parathyroid scintigraphy - Jennings, P A (Division of Nuclear Medicine, 2018)
The purpose of this study is not only to describe scintigraphy in parathyroid imaging and the results obtained but also to discuss the merits and limitations of the technique so that its role in today's climate of cost containment, may better be defined.